Sales Digital Cashier Application Development Using Website (Case Study : Gogo Bakery) - Andrew Louis; Ferdy Riza; Allwine Allwine (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2022)
Cash register technology can simplify and optimize payment transaction management. The activity of buying and selling goods cannot be separated from sales transactions and the sales transaction process cannot be separated from the cashier. GOGO Bakery is a trading shop engaged in the sale of bread. At this store, the transaction process, data processing, and report generation have not been managed computerized, until now this store still has not provided satisfactory and ineffective service, because the payment process at the cashier is not optimal and also the provision of product and price information is not listed properly, which causes consumers to not know the prices and the latest products in the store before buying. In stores, there are usually a lot of item data, transaction data, and others that are impossible to memorize. for that,